2019
DOI: 10.1029/2019ms001635
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating an Adaptive Mesh Refinement Code for Depth‐Averaged Flows Using GPUs

Abstract: Solving the shallow water equations efficiently is critical to the study of natural hazards induced by tsunami and storm surge, since it provides more response time in an early warning system and allows more runs to be done for probabilistic assessment where thousands of runs may be required. Using adaptive mesh refinement speeds up the process by greatly reducing computational demands while accelerating the code using the graphics processing unit (GPU) does so through using faster hardware. Combining both, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…LISFLOOD-FP is a freely available raster-based hydrodynamic model that has been applied in numerous studies from small-scale (Sampson et al, 2012) and reach-scale (Liu et al, 2019;Shustikova et al, 2019;O'Loughlin et al, 2020) to continental and global flood forecasting applications (Wing et al, 2020;Sampson et al, 2015). LISFLOOD-FP has been coupled to several hydrological models (Hoch et al, 2019;Rajib et al, 2020;Li et al, 2020), and it offers simple text file configuration and command-line tools to facilitate DEM preprocessing and sensitivity analyses (Sosa et al, 2020). LISFLOOD-FP includes extension modules to provide efficient rainfall routing (Sampson et al, 2013), modelling of hydraulic structures (Wing et al, 2019;Shustikova et al, 2020), and coupling between two-dimensional flood-plain solvers and a one-dimensional sub-grid channel model (Neal et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…LISFLOOD-FP is a freely available raster-based hydrodynamic model that has been applied in numerous studies from small-scale (Sampson et al, 2012) and reach-scale (Liu et al, 2019;Shustikova et al, 2019;O'Loughlin et al, 2020) to continental and global flood forecasting applications (Wing et al, 2020;Sampson et al, 2015). LISFLOOD-FP has been coupled to several hydrological models (Hoch et al, 2019;Rajib et al, 2020;Li et al, 2020), and it offers simple text file configuration and command-line tools to facilitate DEM preprocessing and sensitivity analyses (Sosa et al, 2020). LISFLOOD-FP includes extension modules to provide efficient rainfall routing (Sampson et al, 2013), modelling of hydraulic structures (Wing et al, 2019;Shustikova et al, 2020), and coupling between two-dimensional flood-plain solvers and a one-dimensional sub-grid channel model (Neal et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…However, for ocean models that are usually developed by Fortran, it is costly not only for the developers to rewrite all the code but also for existing users to reacquaint themselves with the model. We notice that a number of studies on GPU‐accelerated hydrodynamic models have been reported which are based on CUDA Fortran (de La Asunción et al, ; Kim et al, ; Qin et al, ; Yamagishi & Matsumura, ; Zhang & Jia, ; Zhu et al, ). We also adopt CUDA Fortran in this study for the aforementioned reasons.…”
Section: Gpu Implementationmentioning
confidence: 99%
“…In particular, the porting of tsunami models to GPU devices has been a priority of the international tsunami research community in the wake of the devastating 2011 Tohoku Tsunami. Currently, the majority of mainstream tsunami models, mostly based on linear or nonlinear shallow water equations discretized with different orders of accuracy (e.g., Tsunami‐HySEA, MOST, GeoClaw, TUNAMI‐N1, EASYWAVE, and COMCOT), have been accelerated by GPU devices for real‐time tsunami warning purpose at a lower cost (Amouzgar et al, ; Castro et al, ; de La Asunción et al, ; Gidra et al, ; Harig et al, ; Qin et al, ; Satria et al, ). Typically, the computational time for basin‐scale tsunami propagation modeling can be reduced to several minutes, or even tens of seconds in some simplified cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al, 2009;Qi et al, 2014;Dong et al, 2014;. The use of GPUs for shallow water and oceanographic simulations is currently also included in large commercial and academic software packages such as ClawPack (Qin et al, 2019), Telemac (Grasset et al, 2019), TUFLOW (Huxley and Syme, 2016) and MIKE (MIKE Powered by DHI, 2019).…”
Section: Related Workmentioning
confidence: 99%